Analisis karbon operasional di Kampus IPB Dramaga - Putra, Heriansyah; Erizal, Erizal; Purwanto, Mohammad Yanuar Jarwadi; Saptomo, Satyanto Krido; Qayim, Ibnul; Utami, Anisa Dwi; Ramadhanis, Zainab Dwi; Khoirunnisa, Hana (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
The pursuit of a carbon-neutral campus is a critical goal for universities aiming to contribute to global sustainability efforts. As one of the largest universities in Indonesia, IPB University has stated a vision of sustainability as a long-term goal. This study examines the operational carbon at the IPB Dramaga Campus during 2022 to 2024, contribution of transportation aspect and energy consumption. The results show that the operational campus increases from 9,439 to15,937 tons CO2eq or 69% during 2022-2024. The increase in electricity consumption of 53% significantly contributes to carbon production from 10,557,427 kWh to 16,156,871 kWh in 2022 to 2024, respectively. In addition, the increase in the number of cars and motorbikes entering the university also contributes to the increase in operational carbon, with the daily number of cars and motorbikes entering the university increasing from 755 cars and 2,803 motorbikes in 2022 to 2,950 cars and 12,128 motorbikes in 2024. In conclusion, the management of operational carbon, including the use of renewable energy and green transportation, should be addressed to ensure that the target of the carbon balance of the 2030 IPB University can be realized.